TANTANGAN PERAN BIROKRASI SENTRALISTIK, INTEGRASI POLITIK PEMERINTAHAN DAERAH, PREDIKTOR SISTEM KOMUNIKASI NASIONAL BARU - Alex Rumondor (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2014)
Abstract: Indonesia experiences changing from centralized governmental system to be localbased government through autonomy to manage each region. That changing will related to newnational communication system, that are communication condition within government(suprastructure of communication) and communication within society (infrastructure ofcommunication). Communication is understood in its state context with its value system –Pancasila and Constitution 1945, culture and the existing institutions. Within this frameworkbureaucracy communication which is centralistic will face challenge, that is how suprastructurand infrastructure communication can be maintained and operate in the balance way to achievenation-state integration.Keywords: Centralistic Bureaucracy, Regional Government, New National CommunicationSystem Abstrak: Indonesia mengalami perubahan dari sistem pemerintahan sentralisik menjadipemerintah berbasis lokal melalui otonomi untuk mengatur masing-masing daerah. Perubahantersebut akan berkaitan dengan sistem komunikasi nasional baru, yaitu suasana komunikasidalam pemerintahan (suprastruktur komunikasi) dan komunikasi dalam masyarakat(infrastruktur komunikasi). Komunikasi dipahami dalam konteks kenegaraan dengan sistemnilainya Pancasila dan UUD 1945, budaya serta berbagai lembaga yang ada. Dalam kerangkaini komunikasi birokrasi yang masih bersifat sentralistik akan menghadapi tantangan, yaitubagaimana suprastruktur dan infrastruktur komunikasi dapat dipertahankan dan berjalanseimbang untuk mencapai integrasi negara bangsa.Kata Kunci: Birokrasi Sentralistik, Pemerintah Daerah, Sistem Komunikasi Nasional Baru.